Knowledge, attitude and practice of long acting reversible hormonal contraception (LARHC) among women in urban upper Egypt - Mitwaly, Abo bakr A.; Abbas, Ahmed M.; Mohammed, Amal Fathy; Ismail, Alaa M.; Shaamash, Ayman H.; Youssef, Alaa El Din A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The current study aims to assess the knowledge, attitude and practice of long acting reversible hormonal contraception (LARHC) among women in urban upper Egypt. Methods: A cross sectional study which included 902 married women, in the reproductive age, attending the outpatient clinics (Gynecology and family planning) of: 1-Assiut University Maternity Hospital, 2- Sohag University Hospital, and 3-Gehina General Hospital (MOH hospital) with current or previous use of any method of LARHC methods. A Questionnaire file was designed to assay knowledge attitude and practice of clients towards contraceptive methods. All data collected from clients reviewed separately to assess knowledge, attitude and practice of women towards contraceptive methods. Results: The most popular contraceptive method is COCs followed by IUD then DMPA. 99% of studied sample heard with good description about different types of LARHC. 54.9% of studied sample most popular/famous LARHC DMPA, most sources of information on LARHC were, Hospital, Relative/friends and health workers. 94.24% of the studied sample were in favor to use of LARHC, 94.2% of them agree to take a space between births, about 55.4% of them were health child and 61% comfortable lifestyle benefit from birth spacing, 33% of studied sample were maternal health, 68% of them were think/prefer to use implants, 64.5% of them didn’t pregnant while breastfeeding. 11% of sample women never used any contraception before and most reasons for not using contraception are fear of side effects, desire for more children, irregular sexual relationship, and husband opposition. Only 16.6 % of studied sample used LARHC before and most of them used DMPA, however 3 women who used DMPA get pregnant while using it. Conclusions: There is a good level of knowledge between upper Egypt women about LARHC methods.